Changes in the forming aspects of the public service bargains components in determining the general budget policy - Setiyaningsih, Y.; Pramusinto, A.; Kusumasari, B.; Purbokusumo, Y. (American Institute of Physics Inc., 2023)
Public Service Bargains (PSB) perspective is used to analyze the relationship between politicians and bureaucrats based on the roles of both parties. This study aims to discuss how the relationship between politicians and bureaucrats and their interactions in two periods of leadership with different backgrounds, to analyze what aspects of interaction, behavior and power are in the PSB framework, particularly in determining budget policy in general. Discussions about governance and leadership as well as the interaction of politicians and bureaucrats are presented based on information and data obtained from primary data sources through in-depth interviews with bureaucratic leaders, that are the Mayor, Chairman of the Regional Representative Council (DPRD) as legislative bodies, Regional Secretary, and other supporting informants. The qualitative method is processed using NVIVO 12. The main findings in this study are aspects of interaction, behavior and power in two leadership eras with different backgrounds, so that this relationship pattern can be used as a reference in analyzing the relationship between bureaucrats and politicians in the PSB framework. The results of this study can be implemented in determining policies, in this case the general budget determination policy in the City of Magelang. © 2023 Author(s).